Nanorings of Self-Assembled Fullerene C70 as Templating Nanoreactors - Iyer, K.; Saunders, M.; Becker, Thomas; Evans, C.; Raston, C. (The American Chemical Society, 2009)
The extraordinary electronic, mechanical, chemical, and structural properties of fullerenes and nanotubes have stimulated research inthe fabrication of all-carbon superstructures. The structural diversity within these graphene-based families, from C28 fullerene to giant fullerenes containing over 106 carbon atoms, from nanotubes to nanowhiskers, and from 'crop circles' to 'onion rings', suggests that a wide variety of carbon superstructures could be prepared incorporating different properties. Self-assembly provides an avenue to facilitate a bottom-up approach to design and fabricate fullerene based materials of higher complexity. The use of nanoscale templates such as micelles and polyelectrolytes are common place in nanotechnology, whereas the use of fullerene-based super structures as 'nanoreactors' has yet to be recognized. In this article, we present a simple, green route for the bottom-up assembly of C70 fullerene into nanorings using the ubiquitous starch-iodine complex and establish the use of the self-assembled structures as nanoreactors in which silver nanoparticles are prepared.